Biochar como enmienda en las características agronómicas y rendimiento del pasto Panicum máximum cv. Tanzania en Zungarococha - Loreto - 2022 - Babilonia Caceres, Enrique (2022)
The use of biochar in forage production and as carbon sequestration in the soil is an environmental alternative. The present research work is entitled BIOCHAR AS AN AMENDMENT IN THE AGRONOMIC CHARACTERISTICS AND PERFORMANCE OF PASTURE Panicum maximum cv. TANZANIA IN ZUNGAROCOCHA,- LORETO - 2022.” The sowing of the vegetative seed, in experimental units of 6.0 m2 area. Random Complete Block Design (D.B.C.A), with five treatments and four repetitions, the treatments under study were: T0 (0 tons of Biochar/hectare), T1 (10 tons of Biochar/hectare), T2 (20 tons of Biochar/ hectare), T3 (30 tons of Biochar/hectare) and T4 (40 tons of Biochar/hectare), having the following results. That the response of the grass Panicum maximum cv. Tanzania at the highest dose of biochar increases forage yield. Agronomic characteristics such as plant height, coverage percentage, green matter and dry matter, are improved at the highest dose of biochar. That the best yields of green matter and dry matter, at the 5th week, occurred with the T4 treatment (20 t/ha of biochar). Based on the results obtained, the hypothesis proposed in the research work is approved. the highest plant height was achieved with T4 (40 tons of biochar/ha.) which obtained an average of 25.95 cm, and in the total weight of the plant, the highest average was 1110.20 gr/plant and in average weight of the head of 1037.45 grams.